Modern myths, locked minds secularism and fundamentalism in India - Madan, T. N. (New Delhi ; Oxford : Oxford University Press, 2009)
Discussing the ideologies of secularism and fundamentalism in the setting of the religious traditions of India, this book covers Hinduism, Islam and Sikhism.
Previous ed.: 1997.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Secularism -- India; Religious fundamentalism -- India; Hinduism -- India; Islam -- India; Sikhism -- India; India -- Religion